2004
DOI: 10.3164/jcbn.35.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Chemopreventive Effects of Chinese Herbs against Hepatocarcinogenesis

Abstract: SummaryThe chemopreventive effects of seven Chinese herbs against hepatocarcinogenesis were evaluated in vitro . The water extracts from Scutellaria barbata and Hedyotis diffusa among the seven herbs as well as Curcuma zedoaria (positive control), strongly inhibited cell growth of four human hepatoma cell lines; HuH-7 (p53 mutant), PLC/PRF/5 (p53 mutant), HepG2 (p53 wild-type) and Hep3B (p53 null). These two extracts also induced apoptotic cell death of these cell lines, as evaluated by DNA fragmentation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Traditional foods have attracted our attention as a precious source of cancer chemopreventive factors [1]. Seaweeds are traditionally part of the diet of East Asians, particularly the Japanese, and sources of amino acids, dietary fibers, minerals, and vitamins [2].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional foods have attracted our attention as a precious source of cancer chemopreventive factors [1]. Seaweeds are traditionally part of the diet of East Asians, particularly the Japanese, and sources of amino acids, dietary fibers, minerals, and vitamins [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, some free radicals produced in the body escape this defense mechanism, causing damages to the body. One such damage is carcinogenesis due to free radicals [5]. To reduce oxidative injury accumulated over a long period (carcinogenesis), many epidemiological studies have suggested the necessity for the consumption of many antioxidants contained in foods.…”
Section: Prevention Of Cancer By Ginkgo Leave Extracts or Antioxidantsmentioning
confidence: 99%